Sosialisasi Pengoperasian Gadget untuk Mencegah Dampak Judi Online dan Meningkatkan Bisnis Desa Beratkulon - Ghozali Ghozali; Fajar Budiyanto; Zenita Afifah Fitriyani; Trijadi Herdajanto (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Current technological developments require young people to get information easily through gadgets. The ease of internet access that is developing sometimes brings up advertisements that trigger online gambling. However, these activities can be diverted by doing positive activities, namely learning business, so the purpose of this community service is to socialize the operation of gadgets to prevent the impact of online gambling and improve the business of Beratkulon Village. The method used in this community service has three steps, namely, preparation steps, implementation steps, and final steps. The results of this community service are, socialization of the operation of gadgets to help prevent online gambling and utilize business so that positive activities occur among village youth, so that village youth increasingly understand to avoid online gambling activities turning into useful business activities. The hope from the results of this activity is to immediately implement the results of the socialization that is applied so that the quality of human resources in Beratkulon Village is getting better, especially village youth.